Modulation of High-Frequency rTMS on Reward Circuitry in Individuals with Nicotine Dependence: A Preliminary fMRI Study - Tao Wang; Ruiyang Li; Dongyan Chen; Mei Xie; Zhiqiang Li; Huan Mao; Yuting Ling; Xiaoyun Liang; Guojun Xu; Jianjun Zhang (Neural Plasticity)
Although previous studies have shown that repetitive transcranial magnetic stimulation (rTMS) can ameliorate addictive behaviors and cravings, the underlying neural mechanisms remain unclear. This study aimed to investigate the effect of high-frequency rTMS with the left dorsolateral prefrontal cortex (L-DLPFC) as a target region on smoking addiction in nicotine-dependent individuals by detecting the change of spontaneous brain activity in the reward circuitry. We recruited 17 nicotine-dependence participants, who completed 10 sessions of 10 Hz rTMS over a 2-week period and underwent evaluation of several dependence-related scales, and resting-state fMRI scan before and after the treatment. Functional connectivity (FC) analysis was conducted with reward-related brain regions as seeds, including ventral tegmental area, bilateral nucleus accumbens (NAc), bilateral DLPFC, and bilateral amygdala. We found that, after the treatment, individuals showed reduced nicotine dependence, alleviated tobacco withdrawal symptoms, and diminished smoking cravings. The right NAc showed increased FC with right fusiform gyrus, inferior temporal gyrus (ITG), calcarine fissure and surrounding cortex, superior occipital gyrus (SOG), lingual gyrus, and bilateral cuneus. No significant FC changes were observed in other seed regions. Moreover, the changes in FC between the right NAc and the right ITG as well as SOG before and after rTMS were negatively correlated with changes in smoking scale scores. Our findings suggest that high-frequency L-DLPFC-rTMS reduces nicotine dependence and improves tobacco withdrawal symptoms, and the dysfunctional connectivity in reward circuitry may be the underlying neural mechanism for nicotine addiction and its therapeutic target.